Assessing the implementation of monitoring and evaluation systems in the National Treasury - Sithagathaga, Latani Nicolas (University of the Witwatersrand, 2022)
This research study was driven and motivated by the need for continuous public service reform while maintaining good governance and enhanced service delivery in public service institutions. Monitoring and Evaluation (M&E) systems are one of the important instruments used to assess progress made in public service reforms and good governance in the public service. A thorough study was conducted to assess the implementation of M&E in the National Treasury to establish challenges and lessons learned. The literature review process conducted was focused on determining relevant theoretical and legislative frameworks as well as policy and frameworks relevant to public sector reforms, governance and M&E. A qualitative research design method was chosen for this study, using a case study to collect data. The unit of analysis was the National Treasury, and a non-probability sampling approach was used to target key informants from the Strategic Planning Monitoring & Evaluation Unit and other employees from different Divisions of the National Treasury. The primary research data was sourced through a series of semi-structured interviews. Content analysis of key M&E relevant government documents was conducted to understand the M&E. To conduct this assessment, the study posed two important questions. The researcher reviewed literature relating to the established history and description of the National Treasury. The researcher further conducted research problem analysis to understand the history and description of monitoring and evaluation. The researcher has further reviewed the literature on the monitoring and evaluation systems of developed and developing countries in Africa and internationally. From the reviewed literature, the researcher developed a theoretical and conceptual framework to guide the research approach in collecting, processing, and analysis of the research results. The researcher developed an explanatory framework that assists in interpreting the findings. Some of the findings pointed to the following issues. It was not clear from the reports whether the National Treasury lacked the capacity and skills for monitoring and evaluation on the repeated audit opinions as raised by Auditor General or whether it lacked defined structures, processes, that also include roles and responsibilities for monitoring and evaluation; or lacked support and buy-in from management and support staff. It is crucial that the National Treasury M&E system generates high quality performance information on quarterly and annual periods to provide decision makers with critical information. This information should also be provided to public, and other stakeholders with accurate and reliable performance information on reforms and good governance of the organisation. The research concluded that, given the establishment and institutional arrangement elements that were assessed and found to be in place and functional, the National Treasury M&E system has the potential to be sustainable if the recommendations provided in this study are considered and implemented. There were no clear indications of specific challenges that were encountered during implementation and there was a clear process followed in conducting the M&E within the organisation which can be used as lessons by other organisations. The Researcher concluded by providing some recommendations to strengthen the National Treasury’s monitoring and evaluation system.
A research report submitted in 50% fulfilment of the requirement for the degree of Master of Management in the field of Governance (Public Sector Monitoring and Evaluation) to the Faculty of Management, Wits School of Governance, University of the Witwatersrand, 2022
Keywords: Monitoring and evaluation; National Treasury; Evaluation systems; UCTD; SDG-16: Peace, justice and strong institutions